THE USE OF THE MEDICAL PERIPHRASES OF THE UZBEK AND ENGLISH LANGUAGES IN JOURNALISTIC TEXTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Journalism, which is considered as the main factor in the development of language, in its turn, widely uses the possibilities of language, at the same time, contributes to the enrichment of our language through new words and phrases. While such qualities as accuracy, conciseness, compactness, and brilliance in journalistic style texts attract attention, these texts are distinguished by their expressiveness, responsiveness, and effective use of periphrases.